HRM POLICY IN HUMAN RESOURCES DEVELOPMENT AND EMPLOYEE MOTIVATION AND THEIR EFFECT ON EMPLOYEE PERFORMANCE MESIR PONSEL PEMATANGSIANTAR - Rupida Sianipar; Pandapotan Simatupang; Darwin Damanik (Institute of Computer Science (IOCS), 2022)
This study aims to see the effect of development and work motivation on Egyptian employee performance in Pematangsiantar Cellphones. The population of this study is the Egyptian employees of Pematangsiantar Cellphones. The number of samples in this study were 35 data. The research variable consists of two independent variables, namely Development (X1) and Work Motivation (X2), one determining variable is Performance (Y). The results of data collection were then analyzed using Validity Test, Reality Test, Multiple Linear Regression, Partial Test (t Test), Coefficient of Determination Analysis with the help of SPSS Version 25 to test and prove the research hypothesis. Based on the test results, the validity test shows that the calculated r value of each indicator variable of Development and Work Motivation is greater than rtable of 0.3388 so that the indicator of performance is valid. The reliability test of the Development and Work Motivation variable with Cronbach's alpha values ​​of 0.776, 0.960, and 0.927 is greater than 0.6 which means that Development and Work Motivation is reliable or reliable. Independent variables that were tested individually in influencing Employee Performance of Egyptian Mobile Phone Pematangsiantar, Development (coefficient 0.992), Motivation (coefficient 0.391), dominant Development affecting performance. Based on the significance level of the research results that Development and Work Motivation obtained a significance level of 0.000 < 0.05 and 0.034 <0.05. So it can be key that means that development and work motivation have a significant effect on performance. Meanwhile, from the results of the calculation of the coefficient of determination (R2), it can be seen or explained that the independent variable in this study is explained by 69.0% of the dependent variable (0.690) in the Egyptian Mobile Phone Pematangsiantar Employees. While the remaining 31.0% is influenced or explained by other variables that are not included in this research model.